Acute Kidney Injury in Lymphoma: A Single Centre Experience - Muhammad Abdul Mabood Khalil; Hira Latif; Abdur Rehman; Waqar Uddin Kashif; Safia Awan; Zarghona Khalil; Uziar Mushtaq; Maria Ahmad; Muhammad Ashhad Ullah Khalil; Manickam Ranga Sami; Jackson Tan (International Journal of Nephrology)
Background. Acute kidney injury (AKI) is a common but least studied complication of lymphoma. Objective. To determine the frequency and predictors of AKI in lymphoma and to study the impact of AKI on hospital stay and mortality. Methods. Retrospective review of medical records of hospitalized lymphoma patients aged ≥14 years between January 2008 and December 2011 was done. Results. Out of 365 patients, AKI was present in 31.8% (116/365). Multivariate logistic regression analysis showed that independent predictors for AKI included sepsis (odds ratio (OR) 3.76; 95% CI 1.83–7.72), aminoglycosides (OR 4.75; 95% CI 1.15–19.52), diuretics (OR 2.96; 95% CI 1.31–6.69), tumor lysis syndrome (OR 3.85; 95% CI 1.54–9.59), and R-CVP regimen (OR 4.70; 95% CI 1.20–18.36). AKI stages 2 and 3 was associated with increased hospital stay (OR 2.01; 95% CI 1.19–3.40). Conclusion. AKI was significantly associated with sepsis, aminoglycoside, diuretics, presence of tumor lysis syndrome, and use of R-CVP regimen. Presence of AKIN (Acute Kidney Injury Network) stages 2 and 3 AKI had increased hospital stay. AKI was also associated with increased mortality.